Regional Economic Issues, May 2017, Central, Eastern, and Southeastern Europe : A Broadening Recovery. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2017)
Economic growth is broadening in Central, Eastern, and Southeastern Europe. Further ahead, however, growth prospects are tested by a dwindling workforce and weak productivity. Reaching Western European income levels would thus take longer, says the IMF in its Regional Economic Issues update on the region.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet